An integrated model for prediction of hydrologic anomalies for habitat suitability of overwintering geese in a large floodplain wetland, China. (1st April 2023) - Teng, Jiakun; Xia, Shaoxia; Liu, Yu; Duan, Houlang; Yu, Xiubo; Chen, Jiang
Abstract: Climate anomalies and increasing human activities cause a high frequency of extreme hydrological events in wetlands, which has put waterbirds under greater survival pressure than ever. Therefore, it is crucial to predict the impact of this phenomenon on the habitat suitability of waterbirds. This study investigated the response of the goose distribution probability to hydrological variations using the flood duration index (FD), enhanced vegetation index (EVI), and waterbirds GPS tracking data in Poyang Lake. An overwintering geese habitat suitability index (HSI) is built based on the FD, EVI, and threat index and verifies the accuracy of the model simulation. Then, the effects of drought and flood on the goose habitat especially sub-lakes with different connectivity were analyzed. The findings reveal that in dry and flood years, geese will broaden their range of feeding vegetation (more fresh or mature vegetation) in response to environmental deterioration. Both drought and flood can lead to a decline in the HSI, especially flood. Connected sub-lakes are more vulnerable to hydrological anomalies than controlled sub-lakes. This research establishes a scientific foundation for floodplain wetland hydrology management and waterbird conservation. Graphical abstract: Image 1 Highlights: Droughts and floods reduce the habitat suitability of geese, especially floods. An integrated habitat model combining hydrology, vegetation, and human activities. Geese widen the feeding vegetation growth stage to adapt to hydrological anomalies. Controlled sub-lakes are more resistant to hydrological disturbances.